Perspectives of social participation in the context of STS education - Roseline Beatriz; Maria Regina (Uni-pluriversidad, 2014)
Given the diversity of meanings attributed to the prospects of social participation, this article presents a systematization about prospects of social participation found in the context of the STS Education. For this, we investigate two different groups of authors, who develop reflections of this nature (I) in the social context, external to the educational field, and (II) in discussions about STS education. From that, different perspectives of social participation were mapped. Those perspectives were compared with the Brazilian production in STS Education, through the analysis of papers published in national journals and events. Based on this, we propose five categories. These can be arranged in increasing levels of criticism, ranging from the simple recognition of the presence of science and technology to the complex public policy participation. It is expected that such systematization can contribute to situate educational objectives involved in discussions CTS.